2017
DOI: 10.1021/acs.jpcc.7b04483
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Observation of Exciplex Formation and Decay Mediated by One-Dimensional Bridges

Abstract: We report herein unprecedented long-range observation of both formation and decay of the exciplex state in donor (D)−bridge (B)−acceptor (A) linked systems. Zinc porphyrins (ZnP) as a donor were tethered to single-walled carbon nanotube (SWNT) as an acceptor through oligo(pphenylene)s (ZnP−ph n −SWNT) or oligo(p-xylene)s (ZnP− xy n−1 −ph 1 −SWNT) with systematically varied lengths (n = 1− 5) to address the issue. Exponential dependencies of rate constants for the exciplex formation (k FEX ) and decay (k DEX ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The IPCE spectrum matches with that of the FTO/SnO 2 /pinB- p -ph-SWNT (Figure S13c). These indicate that the absorption arising from the porphyrin dimers does not generate the photocurrent, but one from the SWNT moiety solely generates the photocurrent in the FTO/SnO 2 /(ZnP- m -ph) 2 -SWNT device, as also seen in the devices with porphyrin monomer-linked SWNTs. This result is in sharp contrast with analogous photoelectrochemical devices with the FTO/SnO 2 electrodes modified with porphyrin–fullerene linked systems that yield the complete charge-separated state and the resultant photocurrent response from the porphyrin absorption . These photoelectrochemical results also corroborate no formation of the complete charge-separated state by the photoexcitation of the (ZnP- m -ph) 2 -SWNT.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The IPCE spectrum matches with that of the FTO/SnO 2 /pinB- p -ph-SWNT (Figure S13c). These indicate that the absorption arising from the porphyrin dimers does not generate the photocurrent, but one from the SWNT moiety solely generates the photocurrent in the FTO/SnO 2 /(ZnP- m -ph) 2 -SWNT device, as also seen in the devices with porphyrin monomer-linked SWNTs. This result is in sharp contrast with analogous photoelectrochemical devices with the FTO/SnO 2 electrodes modified with porphyrin–fullerene linked systems that yield the complete charge-separated state and the resultant photocurrent response from the porphyrin absorption . These photoelectrochemical results also corroborate no formation of the complete charge-separated state by the photoexcitation of the (ZnP- m -ph) 2 -SWNT.…”
Section: Resultsmentioning
confidence: 97%
“…The fourth TA decay component spectrum exhibits negative signals with a negative peak at 1010 nm in the NIR region, but the sum of the spectra for ZnP 2 •+ and SWNT •– shows downward-sloping negative signals in the NIR region. In addition, the absence of the characteristic absorption bands for the ZnP monomer radical cation (ZnP •+ ) in 600–700 nm and radical anion (ZnP •– ) in 700–750 nm in the fourth decay component spectrum contradicts the formation of a symmetry-breaking charge-separated state , in the porphyrin dimer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For exciplex formation, the distance between electron-donor and electron-acceptor molecules has to be very small, on the order of a few nanometers at most. [11][12][13] However, Nakanotani et al observed exciplex emissions derived from long-distance coupled donor and acceptor molecules with a 10 nm thick spacer layer, 14 and then, Chapran et al, Li et al, and Sych et al also observed similar exciplex emissions with a several nanometer spacer layer, using different types of donor and acceptor molecules. [15][16][17] Colella et al reported that donor and acceptor molecules diluted in a host matrix (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Regarding the electroplex, the decay of the CT excited states only takes place until holes and electrons are, respectively, injected into the donor and acceptor . In general, for both the exciplex and the electroplex, the interaction between donor–acceptor pairs requires intimate contact with each other, usually limited to the distance of a few nanometers. , Recently, it has been proven that an exciplex can be generated from long-range CT interactions, even up to 70 nm . However, the long-range CT-induced electroplex has never been disclosed.…”
mentioning
confidence: 99%